Revived, remixed, revisited [compact disc] - McEntire, Reba (MCA Nashville, 2021)
Featuring 30 total tracks across three discs, this collection spans Reba's entire career and offers something for every Reba fan. Revived was recorded with Reba's touring band. Remixed includes "Little Rock" and "I'm A Survivor." And Revisited, produced by the Grammy award-winning Dave Cobb, strips back songs like "Somebody Should Leave" and"Consider Me Gone."